Modified hard carbon material, preparation method thereof and application of modified hard carbon material in sodium-ion battery

By embedding sodium supplementation agent and sodium ion conductor in hard carbon materials and covering the conductive agent layer, the insufficient performance of traditional hard carbon materials in sodium ion batteries is solved, and efficient sodium ion storage and significantly improved electrochemical performance are achieved.

CN119725452APending Publication Date: 2025-03-28YIBIN SOUTHWEST UNIV RES INST

Patent Information

Application Number
CN202411904036.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The poor performance of traditional graphite in sodium ion storage leads to low first-week Coulomb efficiency, poor rate performance and insufficient cycle performance of sodium ion batteries.

Method used

By embedding sodium supplementation agent and sodium ion conductor in the hard carbon material and covering the conductive agent layer on the surface, a modified hard carbon material with the sodium supplementation agent and/or sodium ion conductor and the externally coated with the electronic conductive agent is formed.

Benefits of technology

It significantly improves the first week of Coulomb efficiency, rate performance and cycle stability of modified hard carbon materials, and is suitable for sodium ion battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725452A_ABST
    Figure CN119725452A_ABST
Patent Text Reader

Abstract

The invention discloses a modified hard carbon material, a preparation method thereof and an application of the modified hard carbon material in a sodium-ion battery, and the modified hard carbon material is prepared by taking a pretreated hard carbon precursor or a high-temperature carbonized hard carbon material and modifying the pretreated hard carbon precursor or the high-temperature carbonized hard carbon material by using a sodium supplement agent and / or a sodium ion conductor and a conductive agent. The composite hard carbon material is provided with a sodium supplementing agent and / or a sodium ion conductor embedded in a hole and an electronic conductive agent coated outside. The sodium supplementing agent or the sodium ion conductor in the holes of the modified hard carbon material can be decomposed in the charging and discharging process, irreversibly consumed sodium ions in the battery circulation process are compensated, the coulombic efficiency and the circulation stability of the material can be improved, the sodium ion conductor can promote diffusion of the sodium ions in the bulk phase and the holes of the hard carbon material, and the battery performance is improved. And the surface electronic conductor coating layer can construct a stable electronic path between particles, so that the improvement of the rate capability and the cycle performance of the material is promoted. The modified hard carbon material is proved to be applied to the sodium-ion battery, so that the electrochemical performance can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, in particular to a negative electrode material for a sodium ion battery, specifically to a modified hard carbon material and a preparation method thereof and application thereof in a negative electrode material for a sodium ion battery. Background Art

[0002] Sodium-ion batteries (SIBs) have become one of the new energy storage technologies that have attracted much attention in recent years due to their advantages such as abundant raw materials, low cost and environmental friendliness. In sodium-ion batteries, the performance of the negative electrode material plays a decisive role in the overall energy density, rate performance and cycle life of the battery. However, due to the large radius of sodium ions (about 0.102nm) and the kinetic limitations of their intercalation and deintercalation processes, traditional graphite performs poorly in sodium ion storage. Therefore, the development of negative electrode materials that can efficiently store sodium ions has become a research focus. Hard carbon, as a composite structure of amorphous and microcrystalline carbon materials, has become one of the most promising negative electrode materials for sodium-ion batteries with its high specific capacity, good cycle stability and excellent rate performance. However, the commercial development of hard carbon materials still faces problems such as low first-week coulombic efficiency, poor rate performance and insufficient cycle performance.

[0003] The low first-cycle Coulombic efficiency of hard carbon materials is mainly attributed to the occurrence of irreversible reactions during the sodium insertion process, such as the decomposition of the electrolyte to form a solid electrolyte interface (SEI) and the irreversible capture of sodium on the surface and in the pores of the material. In addition, the low diffusion rate of sodium ions in hard carbon leads to problems such as poor rate performance and insufficient cycle performance.

[0004] Therefore, the development of negative electrode materials with high first coulombic efficiency, high rate performance and excellent cycle life is the key to the application of sodium-ion batteries. Summary of the invention

[0005] In view of the problems of the prior art, the main purpose of the present invention is to provide a modified hard carbon material, which improves the first-cycle coulombic efficiency, rate performance and cycle performance of the hard carbon material through a multi-dimensional strategy. A preparation method of the modified hard carbon material is provided, and the performance of the modified hard carbon material as a negative electrode material for a sodium ion battery is verified.

[0006] To achieve the above-mentioned invention object, the specific technical solution of the present invention is:

[0007] A modified hard carbon material, wherein at least one of a sodium supplement and a sodium ion conductor is embedded in the pores of a hard carbon precursor, and a conductive agent layer is coated on the surface.

[0008] Preferably, the sodium supplement is one or more of Na2O, NaI, NaI3, Na3N, Na3PO4, Na2HPO4, NaH2PO4, CH3COONa, Na2C2O4, and Na2CO3, and the sodium ion conductor is NaFeO2, NaNa3Zr2Si2PO 12 、NaBr、Na3N、NaF、β″-Al2O3 containing sodium、Na3SbS4、Na2(BH4)0.5(NH2) 0.5 , Na3OBH4, and the hard carbon material precursor is a product formed by one or more of biomass, waste, resin, chemical processed products, etc. after pre-carbonization and / or high-temperature carbonization.

[0009] Further preferably, the hard carbon material precursor is a product formed by one or more of walnut powder, bamboo, wood, waste plastic, waste straw, phenolic resin, epoxy resin, polyamide resin, polyester resin, cyclodextrin, lignin, cellulose, glucose, polymethyl methacrylate or polymaleic anhydride after pre-carbonization and / or high-temperature carbonization.

[0010] Preferably, the conductive agent is at least one of Ag, Cu, Au, Al and their related oxides, nitrides or sulfides.

[0011] Preferably, the mass ratio of the sodium supplement and / or sodium ion conductor to the hard carbon material precursor is 1:3-10000, and the mass ratio of the conductive agent to the hard carbon material precursor is 1:3-10000.

[0012] 2. A method for preparing a modified hard carbon material, characterized in that it comprises the following steps:

[0013] Option A:

[0014] (1) Preparing a hard carbon material precursor: Pre-carbonizing the raw materials at a temperature of 200-750° C. in an inert atmosphere or an oxidizing atmosphere to obtain a hard carbon material precursor having micropores;

[0015] (2) Coating of the conductive agent on the surface of the hard carbon material precursor: dissolving the conductive agent in deionized water to prepare a conductive agent precursor solution, wherein the concentration of the conductive agent is 0.01-10 mol / L, and then dispersing the hard carbon material precursor obtained in step (1) in the conductive agent precursor solution according to a mass ratio of the conductive agent to the hard carbon material precursor of 1:1-10000, stirring at room temperature for 0.5-24 hours, filtering and drying, heating at 100-1200° C. in an inert atmosphere or an oxidizing atmosphere for pre-carbonization treatment for 0.5-24 hours, continuing to heat to 700-1700° C. in an inert atmosphere for high-temperature carbonization for 0.5-24 hours, and cooling to obtain a hard carbon material having a coated conductive agent layer;

[0016] (3) Melting and diffusion of the sodium supplement and / or sodium ion conductor into the pores: The sodium supplement or sodium ion conductor precursor is mixed with a hard carbon material having a conductive agent layer coated thereon in a mass ratio of 1:1-10000, and the mixture is heated until the sodium supplement or sodium ion conductor precursor is melted or decomposed, thereby preparing a modified hard carbon material having the sodium supplement and / or sodium ion conductor embedded in the pores and the electronic conductive agent coated on the surface.

[0017] Option B:

[0018] (1) mixing the sodium supplement and / or sodium ion conductor precursor with the raw materials in a mass ratio of 1:1-10000;

[0019] (2) heating the composite at 100-1200° C. in an inert atmosphere or an oxidizing atmosphere for pre-carbonization treatment for 0.5-24 hours, further heating to 700-1700° C. in an inert atmosphere for high-temperature carbonization for 0.5-24 hours, and cooling to obtain a hard carbon material with a sodium supplement and / or a sodium ion conductor embedded in the pores;

[0020] (3) Depositing conductive agent nanoparticles onto the surface of the hard carbon material obtained in step (2) by atomic evaporation, vapor deposition or atomic layer deposition to prepare a modified hard carbon material having a pore-embedded sodium supplement and / or a sodium ion conductor and a surface-coated electronic conductive agent.

[0021] Preferably, in the scheme A, steps (2) and (3) can be exchanged in order, that is, the sodium supplement and / or the sodium ion conductor are first loaded into the pores of the hard carbon material precursor, and then the coating agent and high-temperature carbonization treatment are performed.

[0022] Preferably, in step (2) of scheme A, the concentration of the conductive agent is 0.05-3 moL / L.

[0023] 3. Application of the modified hard carbon material as negative electrode material for sodium ion batteries.

[0024] The beneficial effects of the present invention are as follows: the present invention discloses a modified hard carbon material, which takes a pretreated hard carbon precursor or a hard carbon material after high-temperature carbonization, and then uses a sodium supplement and / or a sodium ion conductor and a conductive agent to modify it, thereby forming a hard carbon material having a pore-embedded sodium supplement and / or a sodium ion conductor and an externally coated electronic conductive agent. The sodium supplement and / or sodium ion conductor raw materials used in the present invention can be melted and / or decomposed at high temperatures. In the molten state, these materials will enter the pores through capillary action, and / or generate gas to generate more pores during the decomposition process, while the molten condensation products and / or decomposition products can remain in the pores; on the other hand, the conductive agent molecules coated on the surface of the hard carbon material can produce electrostatic adsorption and / or chemical bonding interactions with the hard carbon material and / or its precursor, and can form an effective coating structure on the hard carbon material.

[0025] The sodium supplement or sodium ion conductor in the pores of the modified hard carbon material can decompose during the charge and discharge process, compensating for the irreversible consumption of sodium ions during the battery cycle, thereby improving the coulombic efficiency and cycle stability of the material, and the addition of the sodium ion conductor can promote the diffusion of sodium ions in the bulk and pores of the hard carbon material, improving the rate performance of the material, and the surface electronic conductor coating can build a stable electron path between particles, promoting the improvement of the material's rate performance and cycle performance. The application examples verify that the hard carbon material disclosed in the present invention with an embedded sodium supplement and / or sodium ion conductor and an externally coated electronic conductive agent can be used in sodium ion batteries to significantly improve the electrochemical performance.

[0026] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0028] Figure 1 XRD of hard carbon materials prepared in Example 1 of the present invention and Comparative Example 1;

[0029] Figure 2 The 0.1C first-week charge-discharge curves of the hard carbon materials prepared in Example 1 and Comparative Example 1;

[0030] Figure 3 Cycle curves for preparing hard carbon materials for Example 2 and Comparative Example 2;

[0031] Figure 4Rate curves for preparing hard carbon materials for Example 3 and Comparative Example 3;

[0032] Figure 5 This is a schematic diagram of a hard carbon material prepared in the present invention with a sodium supplement and / or sodium ion conductor embedded in the pores and an electronic conductive agent coated on the outside. DETAILED DESCRIPTION

[0033] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0034] Example 1

[0035] A hard carbon material with a sodium supplement and / or a sodium ion conductor embedded in the pores and an electronic conductive agent coated on the outside, specifically comprising the following steps:

[0036] (1) Preparation of hard carbon material precursor: The dried, crushed and size-sorted walnut powder particles were pre-carbonized at 650°C in a N2 atmosphere, and the obtained powder was then washed and dried with a 1M hydrochloric acid aqueous solution for 24 hours to obtain a hard carbon precursor;

[0037] (2) Preparation of coating agent precursor: Dissolve FeCl3 in deionized water to prepare a 0.3M aqueous solution.

[0038] (3) Mixing and treating the coating agent precursor and the hard carbon precursor: 1 g of the hard carbon precursor was dispersed in 20 mL of the coating agent precursor solution, stirred at room temperature for 2 hours, filtered and dried, heated at 300 ° C in an Ar atmosphere for pre-carbonization for 5 hours, and then heated to 1300 ° C for high-temperature carbonization for 2 hours, and cooled to obtain a hard carbon material with an external coating layer;

[0039] (4) Loading the sodium supplement into the hard carbon pores: The hard carbon material with the coating layer obtained in the previous step was mixed with sodium oxalate in a mass ratio of 1:0.2, and heated at 250°C in an Ar-10% H2 atmosphere for 12 hours to obtain a hard carbon material with Na2O sodium supplement embedded in the pores and Fe conductive nanoparticles coated on the outside, which was labeled as HC-Na2O / NaFeO2-Fe. The sodium oxalate was melted and diffused into the pores and decomposed in the pores. At the same time, a small amount of iron-containing compounds was introduced into the pores in the previous step. The iron-containing compounds were converted into NaFeO2, a sodium ion conductor material with sodium ion conductivity, in this step.

[0040] Comparative Example 1

[0041] The hard carbon precursor treated in step 1 of Example 1 was further carbonized at 1300° C. for 2 hours to obtain an unmodified hard carbon material, which was marked as HC1.

[0042] pass Figure 1 Comparison of the XRD patterns of the hard carbon materials shows that the main XRD pattern is the amorphous peak of amorphous carbon. The diffraction peaks located near 23° and 43° correspond to the diffraction of the (002) and (100) crystal planes of the amorphous carbon materials, respectively. The XRD patterns of the hard carbon materials after external coating and internal embedding of sodium supplementers and sodium ion conductors are basically consistent with the diffraction peaks of the original unmodified materials, without obvious changes. This indicates that the structure of the original hard carbon material remains intact, and the introduced sodium supplementers, sodium ion conductors, and electron conductors are in an amorphous state.

[0043] The hard carbon material with the pore-embedded sodium supplement and / or sodium ion conductor and the externally coated electronic conductive agent prepared in Example 1 and the original hard carbon material prepared in Comparative Example 1 were respectively made into negative electrode sheets, and button cells were assembled with metallic sodium as the counter electrode and a mixed solution of EC / DMC (the volume ratio of EC and DMC was 1:1) containing 1 mol / L NaPF6 as the electrolyte. The charge and discharge curves were measured at 0.1C. Figure 2 As shown. Figure 2 It can be seen that compared with the carbon material prepared in Comparative Example 1, the reversible specific capacity of the hard carbon material prepared in Example 1 having an intrapore embedded sodium supplement and / or a sodium ion conductor and an externally coated electronic conductive agent is increased from 275 mAh / g to 350 mAh / g, and the first-week coulombic efficiency is increased from 68% to 89%.

[0044] Example 2

[0045] A hard carbon material having a sodium supplement and / or a sodium ion conductor embedded in the pores and an electronic conductive agent coated on the outside, wherein the method is to first load the sodium supplement and / or the sodium ion conductor into the pores of the hard carbon material precursor, and then coat the coating agent and perform high-temperature carbonization treatment, and specifically comprises the following steps:

[0046] (1) Preparing a hard carbon material precursor: pre-oxidizing the asphalt in air at 250° C. for 3 hours to obtain a hard carbon material precursor;

[0047] (2) preparing a sodium supplement precursor: dispersing NaI and BiI3 in N'N-dimethylpropyleneurea at a molar ratio of 5:1 to prepare a mixed solution with a mass fraction of 30%;

[0048] (3) Mixing and treating the sodium supplement precursor and the hard carbon precursor: The hard carbon material precursor and the sodium supplement precursor solution are mixed together at a mass volume ratio of 5:1 (g / ml), stirred at 60°C for 3 hours, filtered and dried, and carbonized at 1200°C in an Ar atmosphere for 2 hours to obtain a hard carbon material with pore-embedded Na2O sodium supplement and NaI / Na3Bi sodium ion conductor; the oxygen on the surface of the pre-oxidation hard carbon will convert part of NaI into Na2O, and will continue to react with BiI3 to produce Na3Bi alloy;

[0049] (4) Mixing and processing of coating material and hard carbon material: The hard carbon material and BiCl3 were mixed and milled in a ratio of 1:0.05, with water as the ball milling medium, dried, and heated again at 800°C in an Ar-20% H2 atmosphere for 2 hours to obtain a hard carbon material with Na2O sodium supplement and NaI / Na3Bi sodium ion conductor embedded in the pores and Bi nanoparticles coated on the outside, which was labeled as HC-Na2O / NaI / Na3Bi-Bi. BiCl3 was converted into Bi nanoparticles in a reducing atmosphere and dispersed on the surface of the hard carbon material.

[0050] Comparative Example 2

[0051] The hard carbon precursor in step 1 of Example 2 is carbonized at 1200°C in Ar atmosphere for 2 hours, cooled to room temperature, and then heated at 800°C in Ar-20% H2 atmosphere for 2 hours to obtain a hard carbon material free of sodium supplement, sodium ion conductor and electronic conductor coating layer, marked as HC2.

[0052] HC-Na2O / NaI / Na3Bi-Bi and HC2 were made into negative electrode sheets, metallic sodium was used as the counter electrode, 1 mol / LNaPF6EC / DMC (1:1) was used as the electrolyte, and button cells were assembled to test their cycle performance. The results are shown in the figure. Figure 3 As shown. Figure 3 It can be seen that the reversible specific capacity of HC-Na2O / NaI / Na3Bi-Bi material is significantly higher than that of the unmodified hard carbon material HC, and its cycle stability is not affected.

[0053] Example 3

[0054] A hard carbon material with a sodium supplement and / or a sodium ion conductor embedded in the pores and an electronic conductive agent coated on the outside, specifically comprising the following steps:

[0055] (1) Preparation of a composite solution of a hard carbon material precursor and a sodium supplement: 1 g of phenolic resin was dissolved in ethanol, 0.02 NaH2PO4 was added, and the mixture was stirred and dried at 80°C to obtain a composite precursor; NaH2PO4 was uniformly dispersed inside the framework of the phenolic resin precursor.

[0056] (2) directly carbonizing the composite precursor at 1400° C. in an Ar atmosphere to obtain a hard carbon material with Na3P sodium supplement embedded in the pores; NaH2PO4 is decomposed and converted into Na3P, and the generated H2O molecules and CO2 molecules will form pores inside the hard carbon material, and Na3P is distributed in the pores;

[0057] (4) Under the conditions of vapor pressure of 10-3 Pa and temperature of 760°C, 0.01 g of Ag was deposited onto the surface of 2 g of the above hard carbon material by atomic evaporation to prepare a final hard carbon material with Na3P sodium supplement embedded in the pores and Ag covering the surface, which was labeled as HC-Na3P-Ag.

[0058] Comparative Example 3: 1 g of phenolic resin was dissolved in ethanol, dried with stirring at 80° C., and carbonized at 1400° C. in an Ar atmosphere to obtain an unmodified original hard carbon material, which was marked as HC3.

[0059] HC-Na3P-Ag and HC were made into negative electrode sheets, metallic sodium was used as the counter electrode, 1 mol / L NaPF6 EC / DMC (1:1) was used as the electrolyte, and button cells were assembled to test their rate performance. The results are shown in the figure. Figure 4 As shown. Figure 4 It can be seen that compared with HC3, HC-Na3P-Ag has higher capacity and cycle stability.

[0060] From Examples 1-3 and Comparative Example 3, it can be explained that the sodium supplement or sodium ion conductor in the pores of the modified hard carbon material can decompose during the charge and discharge process, compensating for the irreversible consumption of sodium ions during the battery cycle, thereby improving the coulombic efficiency and cycle stability of the material, and the addition of the sodium ion conductor can promote the diffusion of sodium ions in the bulk and pores of the hard carbon material, improving the rate performance of the material, and the surface electronic conductor coating can build a stable electron path between particles, promoting the improvement of the material rate performance and cycle performance. Through the application examples, it is verified that the hard carbon material disclosed in the present invention with an embedded sodium supplement and / or sodium ion conductor in the pores and an externally coated electronic conductive agent can be applied to sodium ion batteries to significantly improve the electrochemical performance.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A modified hard carbon material, characterized in that: At least one of a sodium supplement and a sodium ion conductor is embedded in the pores of the hard carbon precursor, and a conductive agent layer is coated on the surface.

2. A modified hard carbon material according to claim 1, characterized in that: The sodium supplement is one or more of Na2O, NaI, NaI3, Na3N, Na3PO4, Na2HPO4, NaH2PO4, CH3COONa, Na2C2O4, and Na2CO3; the sodium ion conductor is NaFeO2, NaNa3Zr2Si2PO 12 、NaBr、Na3N、NaF、β″-Al2O3 containing sodium、Na3SbS4、Na2(BH4)0.5(NH2) 0.5 , Na3OBH4, and the hard carbon material precursor is a product formed by one or more of biomass, waste, resin, chemical processed products, etc. after pre-carbonization and / or high-temperature carbonization.

3. A modified hard carbon material according to claim 2, characterized in that: The hard carbon material precursor is a product formed by one or more of walnut powder, bamboo, wood, waste plastic, waste straw, phenolic resin, epoxy resin, polyamide resin, polyester resin, cyclodextrin, lignin, cellulose, glucose, polymethyl methacrylate or polymaleic anhydride after pre-carbonization and / or high-temperature carbonization.

4. The modified hard carbon material according to claim 1, characterized in that: The conductive agent is at least one of Ag, Cu, Au, Al and their related oxides, nitrides or sulfides.

5. The modified hard carbon material according to claim 1, characterized in that: The mass ratio of the sodium supplement and / or sodium ion conductor to the hard carbon material precursor is 1:3-10000, and the mass ratio of the conductive agent to the hard carbon material precursor is 1:3-10000.

6. A method for preparing a modified hard carbon material, characterized in that: The steps include: Option A: (1) Preparing a hard carbon material precursor: Pre-carbonizing the raw materials at a temperature of 200-750° C. in an inert atmosphere or an oxidizing atmosphere to obtain a hard carbon material precursor having micropores; (2) Coating of the conductive agent on the surface of the hard carbon material precursor: dissolving the conductive agent in deionized water to prepare a conductive agent precursor solution, wherein the concentration of the conductive agent is 0.01-10 mol / L, and then dispersing the hard carbon material precursor obtained in step (1) in the conductive agent precursor solution according to a mass ratio of the conductive agent to the hard carbon material precursor of 1:1-10000, stirring at room temperature for 0.5-24 hours, filtering and drying, heating at 100-1200° C. in an inert atmosphere or an oxidizing atmosphere for pre-carbonization treatment for 0.5-24 hours, continuing to heat to 700-1700° C. in an inert atmosphere for high-temperature carbonization for 0.5-24 hours, and cooling to obtain a hard carbon material having a coated conductive agent layer; (3) Melting and diffusion of the sodium supplement and / or sodium ion conductor into the pores: The sodium supplement or sodium ion conductor precursor is mixed with a hard carbon material having a conductive agent layer coated thereon in a mass ratio of 1:1-10000, and the mixture is heated until the sodium supplement or sodium ion conductor precursor is melted or decomposed, thereby preparing a modified hard carbon material having the sodium supplement and / or sodium ion conductor embedded in the pores and the electronic conductive agent coated on the surface. Option B: (1) mixing the sodium supplement and / or sodium ion conductor precursor with the raw materials in a mass ratio of 1:1-10000; (2) heating the composite at 100-1200° C. in an inert atmosphere or an oxidizing atmosphere for pre-carbonization treatment for 0.5-24 hours, further heating to 700-1700° C. in an inert atmosphere for high-temperature carbonization for 0.5-24 hours, and cooling to obtain a hard carbon material with a sodium supplement and / or a sodium ion conductor embedded in the pores; (3) Depositing a conductive agent onto the surface of the hard carbon material obtained in step (2) by atomic evaporation, vapor deposition or atomic layer deposition to prepare a modified hard carbon material having a pore-embedded sodium supplement and / or a sodium ion conductor and a surface-coated electronic conductive agent.

7. The method for preparing a modified hard carbon material according to claim 6, characterized in that: In the scheme A, the order of steps (2) and (3) is exchanged, that is, the sodium supplement and / or the sodium ion conductor are first loaded into the pores of the hard carbon material precursor, and then the coating agent is coated and the high-temperature carbonization treatment is performed.

8. The method for preparing a modified hard carbon material according to claim 6, characterized in that: In step (2) of scheme A, the concentration of the conductive agent is 0.05-3 moL / L.

9. Use of the modified hard carbon material according to any one of claims 1 to 5 as a negative electrode material for sodium ion batteries.

Citation Information

Patent Citations

  • Modified hard carbon negative electrode material for sodium ion battery and preparation method of modified hard carbon negative electrode material

    CN116154175A

  • Porous hard carbon negative electrode material and preparation method and application thereof

    CN116404128A

  • Hard carbon material externally coated with soft carbon and sodium supplement as well as preparation method and application of hard carbon material

    CN117334901A

  • Fabrication of carbon materials modified by fluidizedbed cvd, carbon electrode and lithium secondarybatteries

    KR1020010096073A

Cited By

  • Sodium-ion battery hard carbon negative electrode material and preparation method thereof, negative electrode and sodium-ion battery

    CN121020557A

  • Sodium ion battery hard carbon negative electrode material, preparation method thereof, negative electrode and sodium ion battery

    CN121020557B